An integrated geological and geophysical approach to identify water-rich weathered granite areas during twin tunnels construction: A case study. (May 2023) - Nie, Lichao; Wang, Chengkun; Liu, Zhengyu; Xu, Zhenhao; Sun, Xikui; Du, Yuchao; Wei, Wei
Highlights: Inrush hazards in tunnels passing through water-rich weathered granite zone were described. The link between the resistivity and various weathered granites was established through laboratory tests. An integrated method of investigating the main tunnel with a horizontal pilot tunnel was applied. TBM successfully passed through the water-rich weathered granite areas in the studied areas. The experiences can provide references for the construction of similar investigation projects. Abstract: Several water inrush and mud outburst disasters occurred during the construction of Gaoligongshan tunnel in the water-rich weathered granite terrains. A combination of geological analysis, laboratory experiment, and geophysical investigation was applied to prevent water inrush events and to ensure safety during tunnel construction and operation. First, geological information in the main tunnel was inferred according to an analysis of the horizontal pilot tunnel geological conditions, which was then applied to the electrical resistivity tomography inversion as prior information. Moreover, the link between the resistivity and water-saturated granite samples with different degrees of weathering in Gaoligongshan tunnel was established through laboratory tests. The link was then applied to electrical resistivity tomography results to delineate scale of water-rich weathered granite areas. A combination of geological analysis, laboratory studies, and electrical resistivity tomography measurements was carried out to identify the size, scale, location, and spatial distribution of water-rich weathered granite areas. With the above measures, the main tunnel in Gaoligongshan tunnel was passed through the detection section successfully. Herein, we present a case study and offer a valuable reference for similar projects concerning underground construction in water-rich weathered granite areas in central Yunnan, China.